Projection method with self-adaptive time steps for LES of ignition and extinction in non-premixed jet flames - Yi Liu; Yongqiang Chen; Kulasegaram, Sivakumar (International Journal for Numerical Methods in Biomedical EngineeringInternational Journal for Numerical Methods in Biomedical Engineering, 2010)
In this paper, a modified projection method is combined with a self-adaptive time step procedure to develop numerical scheme for large eddy simulation (LES) of low Ma number turbulent reactive flows. The projection method introduced by Chorin is modified in this study to satisfy the simulation requirement of low Ma number reactive flow. The time step in this computation is automatically determined according to the time scales of both chemical reaction and turbulent fluctuations. This enables the simulation to capture detailed flow structures with less computational time. Numerical simulation of methane-air jet flames is carried out as an example to validate the developed numerical scheme. The mechanism of a simplified 4-step chemical kinetics is applied for the methane-air reaction. The dynamic model is adopted for the turbulent motion of sub-grid scale (SGS). The dynamic similarity model is used as the SGS model for the reaction rate. The LES results satisfactorily depict the ignition process of the turbulent jet flames and illustrate lucid and detailed coherent structures of the fully developed turbulent reactive jet flow. The LES results also exhibit the mechanism and characteristics of local extinction. The method developed in this study provides an effective way to capture more flow details with less computational time. In addition the method also helps one to investigate the mechanism of ignition and local extinction in jet flames. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: diffusion flames; dynamics; Equations; flow; issues; jet flame; kinetics; large eddy simulation; large-eddy simulation; projection method; scheme; self-adaptive time step; Transport; turbulent combustion; turbulent reactive flow